2018
DOI: 10.1111/jam.14072
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Beauveria bassiana and alternative phytosanitary products

Abstract: The natural products tested and used in the field are considered compatible with B. bassiana under laboratory conditions, making possible new studies and the use of these in insect control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, results of some works have shown that neem oil (2.5%) and neem seed extracts, neem gold, Topneem, biospark and exodon (commercialized biological pesticides), show compatibility with all B. bassiana isolates obtained in these works [26,32,53,63,64]. Furthermore, some studies [65,66] have shown that the combination of Azadirachtin (neem extract) with B. bassiana, has an additive effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of some works have shown that neem oil (2.5%) and neem seed extracts, neem gold, Topneem, biospark and exodon (commercialized biological pesticides), show compatibility with all B. bassiana isolates obtained in these works [26,32,53,63,64]. Furthermore, some studies [65,66] have shown that the combination of Azadirachtin (neem extract) with B. bassiana, has an additive effect.…”
Section: Discussionmentioning
confidence: 99%